Turkey’s Refugee Regime Stretched to the Limit? The Case of Iraqi and Syrian Refugee Flows - (:unkn) unknown (My University, 2013)
0

Turkey has long been a land of asylum due to its geographical location as well as shared social, cultural and historical ties with the Balkans, the Caucasus, Europe, and the Middle East. Since the 1980s, the influx of refugees and irregular and transit migrations to Turkey, particularly from the Middle East but also from Africa and Asia, have intensified. In 1988 and 1991 Turkey was confronted with the Iraqi Kurdish refugee flows, and since the onset and intensification of violence in Syria from 2011 onwards, Turkey is trying to cope with a growing number of refugees with its temporary protection regime. The solution Turkey opted for in both crises is the same: creation of no-fly zones and safe havens for refugees outside of Turkish territory and inside the refugees’ country of origin, which has been implemented in the Iraqi case but has yet to find international support in the Syrian case. These two cases are significant, as they reflect the complex shifting nature of the refugee crises and relief efforts in the post-Cold War era, and present important challenges for Turkish policymakers of foreign and refugee policies, particularly in formulating a new refugee and asylum policy that is in line with Turkey’s new foreign policy vision and its emerging regional and global agency. These two crises also reveal the need for a substantial change and update in the Turkish refugee regime that is long overdue.
Keywords: Uluslararası İlişkiler